Exploring the landing speed of digital society PPP projects: A continuous-time event history analysis of 300 projects - Jun Yang; Xiaomei Hu; Zhanyu Liu (PLoS ONE, 2025)
The Public-Private Partnership (PPP) model has become a viable alternative or supplement to traditional approaches in the development of a digital society. However, PPP projects in this domain often face significant landing (the launch of project implementation, typically marked by contract signing and the commencement of operational activities) challenges. Understanding the factors that influence the speed of project landing is thus of considerable practical importance. Based on the theoretical framework of Van Meter and Van Horn, we propose a causal mechanism linking the policy implementation system to the landing speed of digital society PPP projects. Using data from 300 projects, the study empirically tests this mechanism through continuous-time event history analysis. The results indicate that, compared with organizational and actor factors, material resources such as government fiscal resources and regional financial resources have a relatively weaker impact on landing speed. In contrast, internal goal consensus on innovation, internal government coordination, government-business relationship quality, leadership performance demand, and corporate social responsibility all significantly promote faster landing. Conversely, due to low project profitability and market barriers to social capital participation, information enterprise development is negatively associated with landing speed. We provide targeted policy recommendations to enhance the efficiency and timeliness of PPP-driven digital society initiatives.